Generation of embryonic stem‐like cells from in vivo‐derived porcine blastocysts at a low concentration of basic fibroblast growth factor. (6th November 2017) - Cha, H‐J; Yun, JI; Han, NR; Kim, H‐Y; Baek, S; Lee, S‐H; Lee, J; Lee, E; Park, C‐K; Lee, ST
Contents: Although basic fibroblast growth factor (bFGF) is an essential factor supporting the maintenance of porcine embryonic stem (ES) cell self‐renewal and pluripotency, its high cost has limited previous studies, and the development of a low‐cost culture system is required. For these systems, in vivo blastocysts were progressively cultured under various conditions consisting of different culture mediums and/or different feeder cell numbers at a low concentration of bFGF. As the results, the sequential culture of in vivo‐derived porcine blastocysts on 5.0 × 10 5 mouse embryonic fibroblast (MEF) feeder cells in alpha minimum essential medium‐based medium for primary culture, on 2.5 × 10 5 MEF feeder cells in Mixture medium for the 1st subpassage, and on 2.5 × 10 5 MEF feeder cells in DMEM/Ham's F10‐based medium for the post‐2nd subpassage could support the establishment and maintenance of porcine ES‐like cells at the low concentration of bFGF. The established porcine ES‐like cells showed ES cell‐specific characteristics such as self‐renewal and pluripotency. We confirmed that porcine ES‐like cells could be generated from in vivo‐derived porcine blastocysts at a low concentration of bFGF.